BEAUTY CONSTRUCTION ON WARDAH AD VERSION OF "HALAL FROM SCRATCH" - Rosalina, Emilia; Purnama, Fadhli (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
So many images of beauty are depicted through advertisements with various versions of her beauty. Advertisements are vying to penetrate the subconscious space of women. Beauty is an inseparable part of the inherent values of human beings, especially women. Wardah brings a simple vision, fulfilling the need for halal cosmetics. As time goes by, wardah understands the beauty of Indonesian women is in her personality, she shines because she is natural, and elegant because she is down-to-earth. Wardah comes in "Halal version from scratch". The purpose of this study was to find out the beauty construction in the wardah advertisement "halal version from scratch". this study uses John Fiske's semiotic analysis with the Codes of Television theory, namely with three social levels consisting of the level of reality, the level of representation, and the level of ideology. The method used in this study is descriptive qualitative. From the analysis that has been carried out, the results of this study are at the level of reality of women who have fair skin, high nose, medium eyes, thin lips, long hair, using clothes that are not sensual, simple makeup, feminine and have good behavior and can motivate. At the level of reprensentation of close up shooting techniques that place emphasis on the model's face and bright lighting, and the ideological level the role of capitalism to perpetuate the idealism of beauty that is standardized, limited by one race that is white, and does not use a patriarchal cultural system because the wardah advertisement applies the islamic concept where there is a boundary between men and women